운항조건에서 11,000TEU 컨테이너선의 소요마력 저감을 위한 트림변화 연구 - 이준형(Joon-Hyoung Lee); 천장호(Jang-Ho Chun); 김명수(Myoung-Soo Kim); 박범진(Beom-Jin Park); 유용완(Yongwan Yu); 이영연(Young-Yeon Lee); 안해성(Haeseong Ahn); 김영선(Youngsun Kim); 임일진(Iljin Lim) (大韓造船學會 論文集, 2021)
In this paper, the effect of trim variation on the required power of 11,000TEU container ship was investigated under conditions considering the actual operation speed and draft. For each draft condition, the effective power (PE) and delivered power (PD) trends were investigated with changes in trim and ship speed. At this time, the displacement volume was fixed same as the value of the even trim condition and the both sinkage at the fore and after perpendicular are confirmed. The test ship speeds were determined by considering the operating speed. Both numerical and experimental methods were used to analyze the effects of trim variation. Numerical analysis results were used for evaluating the resistance performance, and the self-propulsion performance was estimated using experimental data obtained from model test.